2014
DOI: 10.1155/2014/503618
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study of Ni20Cr Coatings Applied by HVOF Process in ZnCl2-KCl at High Temperatures

Abstract: Corrosion behavior of Ni20Cr coatings deposited by HVOF (high velocity oxygen-fuel) process was evaluated in ZnCl2-KCl (1 : 1 mole ratio) molten salts. Electrochemical techniques employed were potentiodynamic polarization curves, open circuit potential, and linear polarization resistance (LPR) measurements. Experimental conditions included static air and temperatures of 350, 400, and 450°C. 304-type SS was evaluated in the same conditions as the Ni20Cr coatings and it was used as a reference material to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…observed in Inconel 600 in molten NaCl-KCl is due to the high Fe content in this alloy. Studies with Ni20Cr coatings in Cl-rich molten salts do not show any internal damage such as that observed here[13,14]. The corrosion resistance of Inconel 600 is due to the growth of a protective layer of Cr 2 O 3 on its surface.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…observed in Inconel 600 in molten NaCl-KCl is due to the high Fe content in this alloy. Studies with Ni20Cr coatings in Cl-rich molten salts do not show any internal damage such as that observed here[13,14]. The corrosion resistance of Inconel 600 is due to the growth of a protective layer of Cr 2 O 3 on its surface.…”
supporting
confidence: 58%
“…However, on the other hand it has also been suggested that the NiCr-based alloys show better performance than Fe-base alloys. This combined effect has been established in other studies [9][10][11][12][13][14]. This work addresses the corrosion resistance of Inconel 600 in NaCl-KCl mixture (1 : 1 M) at 700, 800, and 900 ∘ C for 100 hours in static air.…”
Section: Introductionmentioning
confidence: 53%
“…Similar depletion processes have been reported in studies of corrosion by molten salts [81][82][83][84][85]. Figure 11 shows the surface morphology of the oxides formed at 900°C.…”
Section: Sem Analysissupporting
confidence: 79%
“…Ni-Cr systems have also been studied as protective coatings; nickel and chromium form highly stable oxides when exposed to an oxidizing environment, providing high resistance to aggressive media. A thorough study was conducted by Porcayo-Calderon [106,107] on the performance of Ni20Cr coating deposited by HVOF and combustion powder spray processes with chloride salts. Regarding the chloride salt, the authors observed that coating performed better than the uncoated stainless steel 304 substrate, especially at high temperature.…”
Section: Corrosion Resistant Coatings In Tes Systemmentioning
confidence: 99%
“…However, corrosion protection in molten salts does not only depend on the material per se, or on the morphology of the manufactured coating, but is strongly influenced by the chemical stability of the metallic element and their compounds, such as oxides and chlorides. Contributions of [106,107] provide a beneficial understanding of the behavior of Ni-, Cr-and Fe-based alloy and open the way to further improvements related to the investigation of coating stability at higher operating temperatures (closer to the CSP regime) and the optimization of the thermal spray deposition.…”
Section: Corrosion Resistant Coatings In Tes Systemmentioning
confidence: 99%